2023
DOI: 10.1039/d3nj00624g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ions on the adsorption of lysozyme protein below its isoelectric point on hydrophilic (OH–Si) and hydrophobic (H–Si) surfaces

Abstract: Lysozyme is a rigid globular protein with four disulfide bonds which is present in human tears, saliva, sweat and milk. In the present study, thin films of this protein are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Additionally, the strong cohesive energy density of such protein films leads to cracking or brittleness of the films. 10 In order to overcome disadvantages, the addition of plasticizers such as glycerol, sorbitol, etc. helps to improve the strength, softness, and flexibility of the protein biofilms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the strong cohesive energy density of such protein films leads to cracking or brittleness of the films. 10 In order to overcome disadvantages, the addition of plasticizers such as glycerol, sorbitol, etc. helps to improve the strength, softness, and flexibility of the protein biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Wang et al reported the preparation of bovine serum albumin (BSA) and lysozyme (Lys) films with antifouling characteristics for coating of medical devices . Antibacterial films are extremely useful against microbial contamination on food packaging and medical devices. , To produce such eco-friendly materials, Lys is the superior candidate because of its excellent film-forming capacity, antibacterial function, easy commercial availability, and low cost. The antibacterial function of Lys films is achieved by the hydrolysis of 1,4-β linkage glycosidic bonds between N -acetylmuramic acid (NAM) and N -acetyl- d -glucosamine (NAG) residues in the bacterial cell walls to destroy Gram-positive bacteria . Lys acts as a major component to enhance the shelf life of unprocessed or minimum processed food .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation